(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the incidence of homicide, age and gender distribution of victims, type of weapons used and the most frequently targeted regions of body in victims of homicide in Rawalakot, Azad Kashmir, AJ&K. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at SKBZH/CMH Rawalakot, AJ&K from Jan 2012 to May 2015. Materials and Methods: Performa was designed for retrospective cohort study. The study was conducted in the mortuary SKBZH/CMH Rawalakot. Consent was implied and relevant information was gathered from the available record. Out of all the cases autopsied during this three and a half year period, 66 were homicidal in nature. Rest of the cases were excluded. Results: Male to female ratio was 5.6:1.Maximum number of victims belonged to 21-40yrs age group. Single injury was present in 85% (n= 56) cases while 15% (n=10) cases had multiple injuries. The most common region of the body targeted was chest 31.8%(n=21) followed by limbs , head and neck and abdomen .The most common tool used to kill was firearm in 75.8% (n=50) cases followed by sharp edged weapon in 18.2% (n=12) cases and others (including RTA, electrocution etc.) in 6.1%(n=4) cases.